2007
DOI: 10.1007/s00435-007-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of protonephridia in Xenotrichula carolinensis syltensis and Chaetonotus maximus (Gastrotricha: Chaetonotida): comparative evaluation of the gastrotrich excretory organs

Abstract: In an attempt to obtain detailed information on the entire protonephridial system in Gastrotricha, we have studied the protonephridial ultrastructure of two paucitubulatan species, Xenotrichula carolinensis syltensis and Chaetonotus maximus by means of complete sets of ultrathin sections. In spite of some diVerences in detail, the morphology of protonephridia in both examined species shows a common pattern: Both species have one pair of protonephridia that consist of a bicellular terminal organ, a voluminous, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…If two or more terminal cells form the suspending structure of the filtration barrier ( Figure 1C), it is called "compound filter" (Neuhaus 1988). It has been shown for several bilaterian taxa that supporting structures may display a large variation of forms (Kieneke et al 2008). This variation might be informative for phylogenetic inferences.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…If two or more terminal cells form the suspending structure of the filtration barrier ( Figure 1C), it is called "compound filter" (Neuhaus 1988). It has been shown for several bilaterian taxa that supporting structures may display a large variation of forms (Kieneke et al 2008). This variation might be informative for phylogenetic inferences.…”
Section: Introductionmentioning
confidence: 97%
“…This hypothesis seemed to find support in Oudemans' (1885), Nawitzki's (1931) and Friedrich's (1935a, b) observations of a direct connection filtration barrier: (C) compound filter is formed by several terminal cells; (D) filter formed by a single terminal cell; (E) transcellular duct. Notes: ECM, extracellular matrix; DC, duct cell; NPC, nephridiopore cell; PC, podocyte; TC, terminal cell; (A, B) modified from Bartolomaeus and Ax (1991); (C-E) modified from Kieneke et al (2008). ; (B) metanephridial system; arrows indicate the direction of filtration as well as secretory and resorption processes in the duct; (C, D) supporting structure for the between the blood fluid and nephridial lumen in certain palaeonemertean species.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of the phylogeny of Thaumastodermatidae showed that, within this family, not only molecular data and morphology are in general accordance, but also that there is homoplasy in the evolution of some cuticular structures. Indeed, additional data, such as the morphology of different organ systems (see e.g., Hochberg & Litvaitis, 2003;Leasi et al, 2006;Kieneke et al, 2008a;Leasi & Todaro, 2008) as well as gene sequence data should also be utilized for classification.…”
Section: Introductionmentioning
confidence: 99%
“…The duct cells bear several microvilli extending into the duct. The duct is either percellular, i.e., its lumen is enfolded by a cell (sensu Kieneke et al 2008, Wg. 1D), or it is formed by two cells so that the lumen is intercellular (Fig.…”
Section: Free-swimming Naupliusmentioning
confidence: 99%